MARKETING STRATEGY TO INCREASE SALES OF ONLINE EYEWEAR BUSINESS (CASE STUDY: LINGKAR KACAMATA) - Ikhrami Nur Jannah; Harimukti Wandebori (Ikatan Dosen Menulis, 2025)
This study explores the internal dynamics and external influences affecting Lingkar Kacamata, aiming to identify key challenges and opportunities for business growth. The research examines the company’s core customer base, evaluates current marketing efforts, and assesses necessary strategic adjustments. Findings reveal that while Lingkar Kacamata benefits from strong brand recognition, loyal customers, and operational strengths—such as personalized service and customer relationships—it faces limitations due to inadequate warehouse space and a shortage of staff. Moreover, the company has been slow to adopt emerging digital marketing trends, including a delayed presence on platforms like TikTok. Externally, rapid technological developments and the shift to online shopping post-pandemic present both opportunities and threats. The study highlights that Lingkar Kacamata’s tech-savvy, youth-oriented target market values affordability and stylish eyewear. However, limited digital outreach hinders market expansion. Addressing these issues is crucial for strengthening the brand, increasing customer acquisition, and enhancing competitiveness in the digital age.